Proposed Prediction Model and Nomogram for Systemic Complications in Patients Undergoing Free Flap Head and Neck Reconstruction - Burkhard, John-Patrik M.; Giger, Roland; Huber, Markus B.; Schaller, Benoît; Little, Ayla; Khalil, Sherin; Engel, Dominique; Löffel, Lukas M.; Wuethrich, Patrick Y. (Frontiers in Surgery, 2021)
Postoperative complications in head and neck surgery are well-known, but a predictive model to guide clinicians in free flap reconstructions has not been established. This retrospective single-center observational study assessed 131 patients who underwent ablative surgery and received free flap reconstruction. Primary endpoint was the occurrence of systemic complications (PSC). Secondary endpoint was the generation of a nomogram of complications according to the CDC classification. In the ordinal regression model, postoperative administration of furosemide [1.36 (0.63–2.11), p < 0.0001], blood loss [0.001 (0.0004–0.0020), p = 0.004], postoperative nadir hemoglobin [−0.03 (−0.07–0.01), p = 0.108], smoking [0.72 (0.02–1.44), p = 0.043], and type of flap reconstruction [1.01 (0.21–1.84), p = 0.014] as predictors. A nomogram with acceptable discrimination was proposed (Somer's delta: 0.52). Application of this nomogram in clinical practice could help identify potentially modifiable risk factors and thus reduce the incidence of postoperative complications in patients undergoing microvascular reconstruction of the head and neck.